The short stories - Hemingway, Ernest, 1899-1961.; Keach, Stacy (New York, NY : Charies Scribners sons, 1953)
"Set in the varied landscapes of Spain, Africa, and the American Midwest, this definitive audio collection traces the development and maturation of Hemingway's distinct and revolutionary storytelling style-- from the plain bald language of his first story to his mastery of seamless prose that contained a spare, eloquent pathos, as well as a sense of expansive solitude"--Container.
An Alpine idyll -- A pursuit race -- Today is Friday -- Banal story -- Now I lay me -- After the storm -- A clean, well-lighted place -- The light of the world -- God rest you merry, gentlemen -- The sea change -- A way you'll never be -- The mother of a queen -- One reader writes -- Homage to Switzerland -- A day's wait -- A natural history of the dead -- Wine of Wyoming -- The gambler, the nun, and the radio -- Fathers and sons.
Unabridged.
Compact disc.
Read by Stacy Keach.
Keywords: Short stories